The Relationship Between Adolescent Knowledge Levels and the Level of Compliance With Masks During the Covid - 19 Pandemic in Ma Nw Apitaik Pringgabaya Subdistrict - Ahyar Rosidi; Rahmiatun Rahmiatun (Jurnal Kewarganegaraan, 2022)
AbstrakSecara global kasus COVID-19 sampai saat ini sudah mencapai 239.437.517 kasus dengan 4.879.235 kasus kematian, kasus COVID-19 sudah menyebar ke berbagai negara termasuk Indonnesia . Pada awal kemunculan COVID â€“ 19 di Indonesia Tahun 2019, Data terbaru 2020 menunjukkan kasus terkonfirmasi COVID-19 sudah mencapai 4.234.011 dari 24 Provinsi, dengan jumlah kasus kematian sebanyak 142.933 kasus. Desain penelitian menggunakan Kuantitatif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh siswa di MA NW Apitaik Kecamatan Pringgabaya dengan jumlah 60 orang. Teknik sampling menggunakan total sampling. Tingkat pengetahuan responden pada kategori kurang sebanyak 47 responden (78,4%), responden tidak ada yang tahu tentang pentingnya memakai masker di masa pandemi, tingkat kepatuhan responden pada kategori tidak patuh sebanyak 55 responden (91,1%), pihak sekolah belum menganjurkan memakai masker. Hasil uji chi square didapatkan hasil uji yaitu 0,000 Î¬ (0,05). Ada hubungan tingkat pengetahuan remaja dengan tingkat kepatuhan memakai makser di masa pandemi Covid-19 di MA NW Apitaik Kecamatan Pringgabaya dengan p Value 0,000.Kata Kunci: Covid-19, Tingkat Pengetahuan, Tingkat Kepatuhan, Penggunaan Masker.Â AbstractGlobally, COVID-19 cases have so far reached 239,437,517 cases with 4,879,235 deaths, COVID-19 cases have spread to various countries including Indonesia. At the beginning of the emergence of COVID-19 in Indonesia in 2019, the latest data in 2020 showed that confirmed cases of COVID-19 had reached 4,234,011 from 24 provinces, with the number of deaths as many as 142,933 cases. The research design uses Quantitative with a cross-sectional approach. The population in this study was all students in MA NW Apitaik, Pringgabaya District with a total of 60 people. The sampling technique uses total sampling. The level of knowledge of respondents in the category was less than 47 respondents (78.4%), respondents did not know about the importance of wearing masks during the pandemic, and the level of respondents' compliance in the non-compliant category was 55 respondents (91.1%), the school did not recommend wearing masks. The results of the chi-square test obtained test results, namely 0.000 Î¬ (0.05). There is a relationship between the level of knowledge of adolescents and the level of compliance with using the mixer during the covid-19 pandemic in MA NW Apitaik, Pringgabaya District with a p-Value of 0.000.Keywords: Covid-19, Level of Knowledge, Level of Compliance, Use of Masks.